Is art history global? - Elkins, James (New York ; London : Routledge, 2007)
- Art history as a global discipline / James Elkins##- Notes on art history in Latin America / Andrea Giunta##- On David Summers's Real spaces / James Elkins##- The modality of spatial categories / Friedrich Teja Bach##- Is a truly global art history possible? / Ladislav Kesner##- The art seminar / participants, Friedrich Teja Bach ... [et al.]##- Assessments / Ralph Ubl ... [et al.]##- Globalizing art history / Shelly Errington.
CCS Gent
Includes bibliographical references and index.
boek